Preventing fraud in biomedical research - Cogan, Elie (Frontiers in Cardiovascular Medicine, 2022)
Scientific fraud represents, to varying degrees, an increasingly important part of medical literature and is estimated to make up nearly 20% of this literature. The increase in the number of articles accessible in preprint without peer review during the COVID-19 pandemic has led to an increase in the accessibility of fraudulent articles. In recent years, the viral increase in the number of predatory journals has contributed to polluting the scientific literature with articles whose content is unverifiable. Given the international nature of biomedical research, there is an urgent need to define unequivocally what is considered scientific fraud. In order to counter scientific misconduct, national and supranational procedures should be implemented to inform researchers at the beginning of their medical and biomedical training. Ethics commissions should implement local procedures for monitoring ongoing research. Finally, the fight against predatory journals requires information for researchers and the availability of tools to identify these journals.